A systematic review and meta-analysis of metal versus plastic stents for drainage of pancreatic fluid collections: metal stents are advantageous - Saunders, Rebecca J.; Neoptolemos, John P. (Surgical endoscopy and other interventional techniques, 2019)
BackgroundThe use of fully covered metal stents (FCSEMS) and specifically designed lumen apposing metal stents for transmural drainage of pancreatic fluid collections has become widespread. A systematic review published in 2015 did not support the routine use of metal stents for drainage of pancreatic fluid collections. However, recent studies have shown conflicting data; therefore a systematic review and meta-analysis was performed.MethodWe conducted a database search for original comparative studies between plastic and metal stents. The random effects model was used to calculate pooled risk ratios (RR) with 95% confidence intervals (CI). Outcomes analysed were clinical success, adverse events and requirement of further intervention.ResultsThe search identified 936 studies, 7 studies with 681 (340 metal, 341 plastic) patients met inclusion criteria and were included in the meta-analysis. Clinical success was achieved in 93.8% versus 86.2% in the metal and plastic groups, respectively, RR 1.08 [95% CI 1.02-1.14]; p = 0.009. Adverse events were reduced for metal stents when compared with plastic (10.2% vs. 25.0%), RR 0.42 [95% CI 0.22-0.81]; p = 0.010. Metal stent usage reduced bleeding (2.8% vs. 7.9%), RR 0.37; [95% CI 0.18-0.75]; p = 0.006. Further intervention was required in 12.4% of patients in the metal stent group versus 26.7% for plastic stents, RR 0.54; [95% CI 0.22-1.29]; p = 0.165.ConclusionsThe use of metal stents for drainage of pancreatic fluid collections is associated with improved clinical success, fewer adverse events and reduced bleeding compared to plastic stents.
First online: 06 September 2018
Gesehen am 15.07.2019